China’s Engagement with the Taliban Government: Realpolitik or Geo-economics? - Touqeer Hussain; Sher Abbas; Rabia Islam; Hidayat Ullah; Omer Ali Asim; Mahnoor Aslam; Naeem Ullah (Dialogue Social Science Review (DSSR), 2025)
China-Afghanistan relations is a strategic shift driven by Realpolitik and Geo-economics. This paper explores Chinese policy objectives in Afghanistan, focusing on security concerns and economic opportunities. China is driven by stabilizing its western border, stopping extremism, and leveraging Afghanistan's geopolitical position in the Belt and Road Initiative (BRI) context. The Taliban's lack of governmental experience, their diplomatic isolation, and their inability to maintain stability challenge China's investments. However, China employs diplomatic realism, economic incentives, and regional alliances, particularly with Pakistan, to overcome these complexities. China's approach, in the context of geopolitical competition against the West and regional actors such as India and Russia, employs security-oriented diplomacy and economic outreach. China's balance between stability and economic interests is analyzed in this paper, and insights into greater power shifts in the region are offered.